Development of ADC14 hypereutectic ALSi alloy based composite reinforced with SiC , Al2O3 and TiB2 through stir casting - Ahmed Bhutto, Aqeel (2021)
The hypereutectic AlSi alloys contain Si more than 12.3 % (eutectic point), and possesses better mechanical properties than eutectic and hypoeutectic AlSi alloys. But the higher percentage of Si in the hypereutectic AlSi alloy caused to result primary and eutectic Si in microstructure during melting, which in turns to hitch the mechanical properties. The proper control of microstructure and addition of common reinforcement materials (SiC, Al2O3, TiB2) in hypereutectic AlSi alloy will improve mechanical properties. Thus, in this research work, ADC14 hypereutectic AlSi alloy based composite reinforced with SiC (5 to 20%), Al2O3 (5 to 15%) and TiB2 (2 to 8%) was developed through stir casting. The mechanical, physical and thermal properties, and microstructure were investigated for the developed composite through ASTM standards. The results showed that tensile strengths and hardness of all the three composites were increased by increasing the weight percentage of all three reinforcements. The maximum values of ultimate tensile strength and hardness were obtained as 115.81 MPa and 69 HV for 20% of SiC and 8% of TiB2 reinforcements respectively. For physical properties, the optimum values were obtained as 2.67 g/cm3 and 0.023% for 8% of TiB2 and 5% of SiC respectively. For thermal properties, the optimum values were obtained as 178 W/mK and 10.7 1/ºC x 10−6 for 20% of SiC and 15% of Al2O3 respectively. Furthermore, the addition of Al2O3 improved the microstructure of ADC14 hypereutectic alloy based composite. And minor porosities were observed in microscopic images. Comprehensively, all three reinforced materials improved the mechanical, physical and thermal properties of the ADC14 hypereutectic AlSi alloy based composite. The development of ADC14 composite may provide some practical knowledge in materials engineering. Also, based on the results of hardness and thermal properties, the developed composite can be applied for automotive part.